Air transport versus high-speed rail : from physics to economics - Hayk Gregorian (Hochschule für Angewandte Wissenschaften Hamburg, 2025)
Purpose – This bachelor thesis compares high-speed rail (HSR) transport with air transport. The investigation considers physical fundamentals, energy consumption, environmental impact, infrastructure and investment, market situations, passenger's selection criteria to choose transportation options, and overall economics. — Methodology – The thesis combines an investigation of physical principles with a literature review. — Findings – Steel wheels on steel rails show by far less rolling resistance to support the train's weight than drag due to lift (induced drag) to support the aircraft's weight. This leads to less energy consumption. HSR trains use electricity from an overhead line. Hence, the environmental impact of HSR also depends much on how the electricity is produced. Airplanes only need an air traffic control environment to connect airports. In contrast, HSR needs infrastructure to connect stations. The amount of necessary infrastructure depends on the geological conditions. For example, crossing mountains means high investment. Longer passages over water are infeasible for HSR. High-speed rail is superior to air transport when connecting megacities because the trains have higher transport capacity, offer higher service frequencies and mission reliability, shorter total travel time, shorter access time to stations, shorter unproductive waiting time in stations and potentially lower travel costs. HSR is a strong competitor to airline services and has replaced some short range flights. A comparison of HSR in different world regions shows differences in the market situation and in passenger's selection criteria for transportation options. — Research limitations – The potential of high-speed rail was investigated mainly on busy routes with high service frequencies. A comprehensive network comparison between high-speed trains and airplanes was not done and could lead to somewhat different results. — Practical implications – The report tries to contribute arguments to the discussion about alternatives to air travel. — Social implications – With more knowledge people can make an educated choice between transport options, can vote with their feet, and can take a firm position in the public discussion. — Originality/value – A general comparison of HSR and air transport from physical fundamentals to economics seemed to be missing.
Keywords: Luftfahrt; Luftverkehr; Hochgeschwindigkeitszug; Flugmechanik; Energieverbrauch; Umweltbelastung; Infrastruktur; Investition; Reisemarkt; Passagier; Verkehrsmittelwahl; Wirtschaftswissenschaften; Aeronautics; Airplanes; Air traffic control; High speed trains; Physics; Energy consumption; Environmental impact analysis; Infrastructure (Economics); Investments; Marketing; Transportation – Passenger traffic; Choice of transportation; Economics; HSR